Assessing the relationships between young adults' travel and use of the internet over time. (July 2019) - Wu, Guoqiang; Hong, Jinhyun; Thakuriah, Piyushimita
Abstract: Although young people's mobility behaviors and their association with information and communications technologies (ICT) usage have been extensively researched, few studies have considered the relationship between changes in the use of ICT over time and young people's travel patterns. This paper explores how use of the Internet during adolescence/late childhood and the degree of change while transitioning from late childhood to adulthood is related to sustainable travel patterns in young adults. We are particularly interested in the mediating role that attitudes towards the environment have on the relationship between early age Internet use and sustainable travel in young adults. The use of rich, longitudinal datasets, the 2004 British Household Panel Survey (BHPS) and the Understanding Society Survey (Wave 4, 2012/14), allow an investigation of these attitudes and relationships for the same people from childhood to adulthood. We use structural equation modeling (SEM) to examine the complex interrelationships between young adults' Internet use over time, their travel modes and attitudes towards the environment, and other related behaviors. Our key finding is that consistently high levels of Internet use between adolescence and young adulthood is associated with the formation of environmental attitudes. While other factors not considered in this study might also have an effect, we find that these attitudes are indirectly but significantly associated with young adults' sustainable travel patterns and behaviors.